Value at risk and bank capital management : Risk adjusted performances, capital management and capital allocation decision making - Saita, Francesco (Amsterdam ; Boston : Elsevier Academic Press, 2007)
This book presents the measurement of market risk and credit risk in one well-structured book.Aggregation methodology is also presented in detail. The inclusion of real-life examples is also a great benefit to the reader.
Value at risk, capital management, and capital allocation -- What is 'capital' management? -- Market risk -- Credit risk -- Operational risk and business risk -- Risk capital aggregation -- Value at risk and risk control for market and credit risk -- Risk-adjusted performance measurement -- Risk-adjusted performance targets, capital allocation, and the budgeting process.
Includes bibliographical references and index.
aug 07/06/13
Loans
Keywords: Bank capital; Banks and banking -- Risk management